Physico-chemical properties of the oils and fat from crotalaria cleomifolia seeds - Noor Wini Mazlan,; Ikram M. Said, (Universiti Kebangsaan Malaysia, 2011)
The seeds of C. cleomifolia (locally known as kacang hantu) collected along Simpang Pulai - Berinchang Road, Cameron Highlands, was defatted with hexane and the resulting oil was analysed for their physico-chemical properties. The percentage yield of the oil was calculated as 5.3%. The acid value (1.2%), iodine value (85), peroxide value (0.6), saponification value (192.0) and unsaponifiable matter (2.3%) were determined to assess the quality of the oil. The physico-chemical characterisation showed that C. cleomifolia seeds oil is unsaturated semi-drying oil, with high saponifi cation and acidic values. The fatty acid composition of C. cleomifolia seed oil was determined by Gas Chromatography and Gas Chromatography-Mass Spectrometry (ToF). The seed oil of C. cleomifolia contained linoleic acid (57.59%) and palmitic acid (5.07%), the most abundant unsaturated and saturated fatty acids, respectively. The polyunsaturated triacylglycerol (TAG) in C. cleomifolia seed oil determined by reverse phase High performance Liquid Chromatography; contained as PLL (18.04%) followed by POL + SLL (11.92%), OOL (7.04%) and PLLn (6.31%). The melting and cooling point of the oil were 16.22°C and -33.54°C, respectively.